Research handbook on alternative finance - Allen, Franklin; Qian, Meijun; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2024)
"Promoting a comparative perspective, this comprehensive Research Handbook aids in the understanding of alternative finance and its values in a global setting. Readers are encouraged to view alternative finance through the lens of economic mechanisms rather than terminology. Providing a holistic review of alternative finance, this timely Research Handbook emphasizes the development dynamics between financial practices and industry, financial structures, economic considerations and technology development. Chapters examine each individual type of alternative finance and explain their network advantages, such as their responsiveness to cultural structures and business conditions, bringing to light how significant modern developments like technological advancements may lead to dramatic changes in financial systems. Ultimately, they expand on the great variation of alternative financial practices worldwide. Balancing theory, practice and policy considerations, this Research Handbook will be essential for academics and researchers pursuing the study of finance, banking, and international business. It will additionally be highly beneficial for policy makers involved in the development of financial systems and financial regulators"--
Contents: 1. Theories, practices, and prospects of alternative finance / Franklin Allen and Meijun Qian -- Part I: Alternative finance in business transactions: Trade credit -- 2. Production networks and trade credit / Mariassunta Giannetti -- 3. Trade credit: Theory and evidence for emerging economies and developing countries / Robert Cull, Chorching Goh and L. Colin Xu -- 4. Trade credit supply and usage during normal and crisis times: A recent review of literature / Jeffrey Jou, Lei Li and Teng Wang -- Part II: Alternative finance within business groups and stakeholders -- 5. Internal capital markets of korean chaebols / Jieun Im, Woojin Kim and Inmoo Lee -- 6. Executive inside debt compensation / Shawn Huang and Juan Manuel Sanchez -- Part III: Alternative finance through social networks -- 7. Theoretical perspectives on social relationships in informal financing / Samuel Lee and Petra Persson -- 8. Family loans and family firms / Charilaos Mertzanis -- Part IV: Technological transformation and regulatory challenges -- 9. The evolution of p2p lending / Jefferson Duarte, Stephan Siegel and Lance Young -- 10. Alternative financial institutions in China / Nan Li and Meijun Qian -- 11. Managing, preserving and unlocking wealth through fintech / Grace Headinger, Lauren Cohen and Zhaoheng Gong -- Part V: Comparative perspective and intrinsic competitiveness -- 12. International comparison of alternative finance / Franklin Allen, Elena Carletti, Meijun Qian and Patricio Valenzuela -- 13. The impact of culture on finance / Lee Pinkowitz and Rohan Williamson -- 14. The competitiveness of alternative finance / Franklin Allen and Meijun Qian.
Includes bibliographical references and index.
Keywords: elektronické knihy; electronic books; Finance -- Social aspects; Finance -- Government policy